1999
DOI: 10.1007/s003300050801
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the breast from rhabdomyosarcoma: appearances on MRI

Abstract: The authors report a case of blood-borne bilateral metastatic breast disease of alveolar rhabdomyosarcoma (RMS) in a 21-year-old patient. The possibilities of mammography, ultrasound, and MRI in the early detection of breast metastases and their appearance on these modalities are discussed. Whereas mammography rendered no additional information due to dense breast parenchyma and ultrasound showed only a solitary tumor without definite criteria of malignancy, multifocal bilateral spread was verified with MRI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 8 publications
3
37
0
6
Order By: Relevance
“…Previous reports of rhabdomyosarcoma metastases to the breast (1,2,3,13) demonstrated that a poor prognosis despite treatment, and relapse of this aggressive tumour, was observed in most patients (Table 1). Early diagnosis is recommended when suspicious lesions are detected in patients with primary rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports of rhabdomyosarcoma metastases to the breast (1,2,3,13) demonstrated that a poor prognosis despite treatment, and relapse of this aggressive tumour, was observed in most patients (Table 1). Early diagnosis is recommended when suspicious lesions are detected in patients with primary rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The primary tumor most commonly originates from the extremities. These tumors are also mostly of the alveolar subtype (2). Bilateral involvement is between 8% and 25% (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases occur in adolescent females, and the most common primary site is the extremity. Breast metastasis from pleural RMS is extremely rare (5). The longest survival is known to be 16 months from the first diagnosis due to a poor prognosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…5 Although sonography is useful in this setting, very few reports have described the sonographic appearance of rhabdomyosarcoma breast metastases. 2,6 In addition, metastasis to the breast can be an initial clinical manifestation of rhabdomyosarcoma in most cases. 4 For these reasons, the sonographic findings of rhabdomyosarcoma in the breast need to be emphasized.…”
Section: Discussionmentioning
confidence: 99%